A novel approach for in-situ soot size distribution measurement based on spectrally resolved light scattering. (March 2019) - Bouvier, M.; Yon, J.; Lefevre, G.; Grisch, F.
Highlights: Soot angular and spectrally resolved light scattering measurements are reported miniCAST soot with different size and amount of organic carbon are investigated. Soot size distributions are determined based on only two scattering angles. The inversion process is validated with independent SMPS measurements. Spectral dependence of the scattering function F (m) is also determined. Abstract: The present study demonstrates the exploitation of the spectral elastic light scattering technique. Additional information provided by the spectral response of the light scattering signals enables the measurement of the soot size distribution with only two scattering angles. It also provides quantitative data on the spectral dependence of the soot optical index, which is related to the soot chemical composition. The measurement principle consists in dividing the scattered spectra collected at two scattering angles and processing this ratio using the Rayleigh–Debye–Gans theory for Fractal Aggregates (RDG-FA). It is shown that the median diameter of gyration and geometric standard deviation of a lognormal soot size distribution can be determined without any prior information on key parameters such as the fractal prefactor, particle primary diameter, aggregate number density and soot optical properties. A proof of concept was performed on soot particles produced by a miniCAST generator by comparing the optical results with the soot size distributions measured by SMPS. A statistical Bayesian inversion approach was used to determine posterior distributions with a particular emphasis on their uncertainty quantification.